Using Excel and GSP as Computer-Based Mathematical Tools to Assist Secondary Students Setting up Models with Exponential and Cosine Functions (Research Journal of Mathematics & Technology, 2022)
Although Vietnamese secondary students are quite good in solving problems with given mathematicalmodels or partial modelling, but they feel difficult in creating their own mathematical models to solvenon-routine realistic problems. Influenced by a focus on modelling with computer-based mathematicaltools (CBMT), we will try to describe and give some situations that involved Vietnamese students insetting up and using models to solve real-world problems. We introduced the cycle of modelling withexponential and sinusoidal functions by using Microsoft Excel (2007) and GSP (version 5) as computer-based mathematical tools. In this article, we use Microsoft Excel as an automatically CBMT to set upexponential model, and the GSP as dynamically CBMT to make sinusoidal model. The results showedthat setting up models with CBMT created an active learning environment in the mathematicsclassrooms and secondary students to construct a specific cycle with some concrete steps to solve real-life problems.